Sodium Zirconium Cyclosilicate among Individuals with Hyperkalemia - Bruce Spinowitz; Steven Fishbane; Pablo E. Pérgola; Simon D. Roger; Edgar V. Lerma; Javed Butler; Stephan von Haehling; Scott Adler; June Zhao; Bhupinder Singh; Philip T. Lavin; Peter A. McCullough; et al. (2019)
Oral sodium zirconium cyclosilicate (formerly ZS-9) binds and removes potassium via the gastrointestinal tract. Sodium zirconium cyclosilicate-associated restoration and maintenance of normokalemia and adverse events were evaluated in a two-part, open label, phase 3 trial.In the correction phase, adult outpatients with plasma potassium ≥5.1 mmol/L (i-STAT Point-of-Care) received sodium zirconium cyclosilicate 10 g three times daily for 24-72 hours until normokalemic (potassium =3.5-5.0 mmol/L). Qualifying participants entered the ≤12-month maintenance phase and received sodium zirconium cyclosilicate 5 g once daily titrated to maintain normokalemia without dietary or medication restrictions. Prespecified primary end points were restoration of normal serum potassium values (3.5-5.0 mmol/L) during the correction phase and maintenance of serum potassium ≤5.1 mmol/L during the maintenance phase. Adverse events were assessed throughout.Of 751 participants, 746 (99%) achieved normokalemia during the correction phase (mean serum potassium =4.8 mmol/L; 95% confidence interval, 4.7 to 4.8) and entered the maintenance phase; 466 (63%) participants completed the 12-month trial. Participants were predominantly white, men, and age ≥65 years old; 74% had an eGFR<60 ml/min per 1.73 m2, and 65% used renin-angiotensin-aldosterone system inhibitors. Mean time on sodium zirconium cyclosilicate was 286 days. Mean daily sodium zirconium cyclosilicate dose was 7.2 g (SD=2.6). Over months 3-12, mean serum potassium was 4.7 mmol/L (95% confidence interval, 4.6 to 4.7); mean serum potassium values ≤5.1 and ≤5.5 mmol/L were achieved by 88% and 99% of participants, respectively. Of 483 renin-angiotensin-aldosterone system inhibitor users at baseline, 87% continued or had their dose increased; 11% discontinued. Among 263 renin-angiotensin-aldosterone system inhibitor-naïve participants, 14% initiated renin-angiotensin-aldosterone system inhibitor therapy. Overall, 489 (66%) participants experienced adverse events during the maintenance phase, and 22% experienced a serious adverse event. Of eight (1%) deaths, none were considered related to sodium zirconium cyclosilicate. Nine (1%) and 34 (5%) participants experienced serum potassium <3.0 and 3.0-3.4 mmol/L, respectively.After achieving normokalemia, individualized once daily sodium zirconium cyclosilicate was associated with maintenance of normokalemia without substantial renin-angiotensin-aldosterone system inhibitor changes for ≤12 months.